2010
DOI: 10.1108/00070701011034420
|View full text |Cite
|
Sign up to set email alerts
|

Do businesses get the food poisoning they deserve?

Abstract: PurposeFood poisoning remains a major public health problem and 2009 has seen major outbreaks with both financial and social implications. The aim of this paper is to examine whether a business gets the food poisoning it deserves and to assess the role of management including food safety culture in outbreaks.Design/methodology/approachFactors influencing the likelihood of a business causing food poisoning are considered and discussed using four categories or variables. These are then applied in a case study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The cavalier attitude toward food safety was further reinforced by William Tudor's falsifying of documents to deliberately hide potential difficulties. Although foodborne illness may not always be completely preventable, Griffith (2010) concluded that the risk of a business causing foodborne illness is, to a large extent, a consequence of its own activities.…”
Section: John Tudor and Son 2005mentioning
confidence: 97%
See 1 more Smart Citation
“…The cavalier attitude toward food safety was further reinforced by William Tudor's falsifying of documents to deliberately hide potential difficulties. Although foodborne illness may not always be completely preventable, Griffith (2010) concluded that the risk of a business causing foodborne illness is, to a large extent, a consequence of its own activities.…”
Section: John Tudor and Son 2005mentioning
confidence: 97%
“…Evidence provided by employees of John Tudor & Son and EHOs, and documented by photography and video, indicated that cleaning of the facility and its equipment was inadequate; poor maintenance and damaged construction provided physical barriers to proper cleaning; staff were not adequately trained and had poor hygiene habits; and meat with off-odors that indicated spoilage was camouflaged with spices rather than being removed from the food chain (Pennington, 2009). Griffith (2010) told the inquest the food safety culture set by William Tudor raised grave concerns. With the focus set on profit, employees at John Tudor & Son ignored microbiological hazards and undertook actions that increased the potential for cross-contamination from raw meats to cooked.…”
Section: John Tudor and Son 2005mentioning
confidence: 97%
“…Overall discussion and conclusions Notified or known cases of foodborne disease represent the tip of the iceberg (Griffith, 2010;Tam et al, 2011) and the consequences of failing to provide safe food are becoming more severe for victims, businesses and even countries. Success in food safety must not just be to conform to requirements but to achieve a successful business with satisfied safe customers.…”
Section: Positive and Negative Behavioural Consequencesmentioning
confidence: 99%
“…The lack of a full system of food safety management and poor food safety performance associated with several factors (e.g. population growth, growth of highly vulnerable population groups, increased food production and distribution, and changes in consumer behavior towards a preference for high-risk foods) can contribute to the incidence of FBD 10,11 . Therefore, identify the differences between food services, assessing associated factors to food safety performance, can assist the developing of strategies for food safety management.…”
Section: Introductionmentioning
confidence: 99%